IMAGEN CORPORATIVA DEL HOSPITAL GENERAL DEL IESS DE BABAHOYO - Barahona Coello, Diana Carolina (2018)
The Ecuadorian Institute of Social Security (IESS) is a decentralized public entity, created by the Political Constitution of the Republic of Ecuador, endowed with normative, technical, administrative, financial and budgetary autonomy, with legal status and its own assets, as it declares in Article 16 of the Social Security Law, (National Congress of Ecuador, 2011), is a fundamental part of the general insurance of individual and family health specialized IESS and is responsible for protecting the insured and his family in the contingencies of disease and motherhood.